Arachniodes hehaii (Dryopteridaceae), a new fern from Guizhou, China - Lu, Ngan Thi; Gao, Xin-Fen; Zhang, Li-Bing (Phytotaxa, 2019)
A new fern of the genus Arachniodes (Dryopteridaceae), A. hehaii, is described and illustrated from a cave entrance in southwestern China’s Guizhou Province. The new species is similar to A. chinensis, but differs in the color of stipe scales, lamina width and shape, the morphology of lamina apex, and indusium thickness.